Expression and significance of cathepsin C and cathepsin D during pregnancy and Preeclampsia - Jingzhe Song; Nan Zhu; Xinchen Pan; Lu Guo; Xiang Kong (BMC, 2023)
Abstract Background Cathepsin C (Cat C) is involved in the inflammatory-immune system and can be degraded by cathepsin D (Cat D). Preeclampsia (PE) and the inflammation-immunity relationship is currently a hot research topic, but there are still few studies. The aim was to investigate the expression and significance of Cat C and D in the serum of nonpregnant women, patients in various stages of pregnancy and patients with PE, and in the placenta of patients with normal pregnancy and PE. Methods Sixty young healthy nonpregnant women were selected: 180 normal pregnant women, including 60 each in the first, second, and third trimesters, and 100 women with PE, including 39 women with severe preeclampsia. The levels of Cat C and D in serum were detected by enzyme-linked immunosorbent assay (ELISA), and the expression levels of Cat C and D in placentas were detected by immunohistochemistry (IHC). Results The serum of Cat C in the first trimester was significantly lower than that in the nonpregnant group (P < 0.001), whereas Cat D was significantly higher than that in the nonpregnant group (P < 0.01). The levels of Cat C and D in the second trimester and third trimester were significantly higher than those in the first trimester (P < 0.05), but there was no significant difference in Cat C and D between the second trimester and third trimester. The levels of Cat C in the serum and placentas of patients with PE were significantly higher than those in the third trimester (P < 0.001) and positively correlated with the severity of PE (P < 0.001), whereas the levels of Cat D in the serum and placentas of patients with PE were significantly lower than those in the third trimester (P < 0.001) and negatively correlated with the severity of PE (P < 0.001). Age, primigravida proportion, and body mass index were significantly higher in the PE group than in the control group (P < 0.05), which were high-risk factors for PE. Conclusions Cat C and D are associated with the maintenance of normal pregnancy. In patients with preeclampsia, a significant increase in Cat C and a significant decrease in Cat D levels may lead to the occurrence and development of preeclampsia.